Effect of crosslinking reagents and hydroxypropylation levels on dual-modified sago starch properties - Wattanachant, Saowakon; Muhammad, K.; Mat Hashim, D.; Abd. Rahman, R. (Elsevier Science, 2003)
Chemical modification is usually carried out to overcome the unstable properties of native sago starch and improve its physical properties during processing. In this study, dual-modification of sago starch was carried out. The first stage of modification was hydroxypropylation, using propylene oxide at levels ranging from 6 to 12%. This was followed by crosslinking, using three different types of crosslinking agents: a mixture of sodium trimetaphosphate (STMP) and sodium tripolyphosphate (STPP), phosphorus oxychloride and epichlorohydrin. Through hydroxypropylation, it was found that there was a significant increase in molar substitution which in turn induces an increase in crosslinking and this was seen from the marked increase in phosphorus content and degree of substitution. This was accompanied by a significant decrease in paste clarity, swelling power and solubility compared to that of the native starch. Starch that was hydroxypropylated with 10-12% propylene oxide and crosslinked by a mixture of 2% STMP and 5% STPP produced modified starch with the most desirable properties in that it exhibited no viscosity breakdown, high acid resistance, high freeze-thaw stability and improved gel texture.